Optimal chiller loading solution for energy conservation using Barnacles Mating Optimizer algorithm - Mohd Herwan, Sulaiman; Zuriani, Mustaffa (Elsevier B.V., 2022)
This paper proposes an application of evolutionary optimization algorithm, Barnacles Mating Optimizer (BMO) to solve the optimal chiller loading (OCL) problem for minimization of the power consumption in the multi chiller system. BMO mimics the mating behaviour of barnacles in nature. To generate new off-springs, the concept of Hardy–Weinberg principle is adopted for exploitation process and the sperm-cast process is treated as exploration behaviour of BMO. OCL on the other hand is the problem of finding the combination of partial load ratio of each chiller to obtain the minimum energy consumption in air-conditioning system. To demonstrate the effectiveness of proposed BMO, it is tested on three different chiller systems. The obtained results from BMO are compared with other well-known optimization algorithms in the literature. The obtained comparison results indicate that proposed BMO is effective to reach minimum energy consumption for solving the OCL problem.